A combined algorithm to the 2D lattice model for protein folding. (6th July 2010) - Lu, Hengyun; Yang, Genke; Yeung, Lam Fat
This paper presents a novel search strategy for protein folding by combining genetic algorithm (GA) with extremal optimisation (EO). In the proposed algorithm, a constrained structure is proposed to reduce the complexity of algorithm. EO quickly approaches near-optimal solutions and GA generates an improved generation of global approximations. We demonstrate that the marriage of GA and EO can be applied successfully to the protein folding problem. The results show that the algorithm can find these best solutions so far for the listed benchmarks. Within the achieved results, the search converged rapidly and efficiently.